High-Temperature microwave properties and phase transitions of ultramafic nickel ores. (1st October 2021) - Forster, J.; Elliott, R.; Boucher, D.; Bobicki, E.R.
Highlights: Presents the fundamentals pertaining to the microwave treatment of ultramafic ores. High temperature X-ray diffraction analysis showed the transition to heazlewoodite. Conventional heating tests and thermodynamic modelling supported the microwave tests. Abstract: The mining of ultramafic ores is required to meet society's continued demand for nickel. These deposits, however, are difficult to process due to their high serpentine content. Serpentine, a gangue mineral, increases slurry viscosity, slime-coats the valuable Ni-bearing mineral pentlandite, and reports to and dilutes the froth during flotation via the formation of bubble-fibre aggregates. Microwave pre-treatment can be used to convert the serpentine gangue to olivine, which should improve ore processing. However, the fundamental microwave properties and heating behaviour of ultramafic ores must be understood to develop a robust process. Microwave heating curves were developed for, and high temperature permittivity analysis was conducted on, two ultramafic nickel ores (Pipe and OK ore). Subsequently, TGA/DSC (thermogravimetric analysis/differential scanning calorimetry) and HTXRD (high-temperature x-ray diffraction) tests, along with a thermodynamic analysis using FactSage 7.3, were done to explain the heating behaviours and permittivity data. An unusual peak in the permittivity data was detected at 950 °C for the Pipe ore with both increasing and decreasing temperature; however, no phase transitions were detected in the TGA/DSC analysis. HTXRD of the Pipe ore revealed the presence of heazlewoodite at higher temperatures (950 to 1100 °C). Thermodynamic modeling of the Pipe ore system suggests that melting at higher temperatures is responsible for the decrease in the permittivities of this ore. To mitigate the melting and clumping of the ore particles, it is necessary to ensure that the processing temperature does not exceed 800 °C during microwave treatment. The OK ore, which contained less microwave response minerals than the Pipe ore, reached a maximum temperature of 500 °C after only 5 min of heating time, and therefore overheating was not an issue.